Influential Factors of Evidence-Based Energy Policy-making: Government Regulation on Targeting Renewable Energy in Indonesia - Wati Hermawati; Prakoso Bhairawa Putra; Dudi Hidayat; Ishelina Rosaira Poerbosisworo (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2016)
The paper is based on research identifying lessons and approaches in making energy policy and scrutinizes whether empirical evidence–based energy policy exists in Indonesia. Empirical evidence–based energy policy has the potential to reduce poverty as well as have a greater impact on the economic performance of individuals, communities and the government. In this study, we used document analysis and key informant interviews to explore empirical evidence input in energy policy-making. The results of the analysis revealed the following three points. First, there are a range of limitations in the process of energy policy-making as well as in getting an evidence inputs from concerned institutions such as universities, R&D institutions, and industries. Second, the process in making energy policy went through several stages and was not always in sequences, starting from problem identification, needs identification, advocacy, information gathering, policy drafting, and approval obtainment from the institutions concerned. Third, the most influential factor in the formulation of this energy policy is the factor of power and authority instead of knowledge and evidence. The limitations have demonstrated insufficient evidence in the policy-making. Finally, the paper suggests that a working group for data and information gathering should be created.